2021
DOI: 10.1097/aco.0000000000001059
|View full text |Cite
|
Sign up to set email alerts
|

Human factors affecting intraoperative patient safety

Abstract: Purpose of reviewThis review addresses the importance of some of the human factors for intraoperative patient safety with particular focus on the active failures. These are the mishaps or sentinel events related to decisons taken and actions performed by the individual at the delivery end of a system. Such sentinel events may greatly affect intraoperative patient safety. Recent findingsIntimidating, aggressive and disruptive communication is a cause of adverse staff interaction, which may then represent an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…A recent systematic review shows that unacceptable behaviour negatively affects HCPs’ clinical performance and patient outcomes 24. Disruptive behaviour may also impact the HCPs' psychological safety and hence patient safety 25. One of the key features of a PSC is HCPs feeling psychologically safe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review shows that unacceptable behaviour negatively affects HCPs’ clinical performance and patient outcomes 24. Disruptive behaviour may also impact the HCPs' psychological safety and hence patient safety 25. One of the key features of a PSC is HCPs feeling psychologically safe.…”
Section: Discussionmentioning
confidence: 99%
“…It could, however, also be that the team members with a more positive perception of PSC could have a positive influence on team members with a less positive perception. Training teams to understand human factors and team skills are initiatives that can improve PSC 25 31. Several reviews have demonstrated an effect of training emergency teams such as trauma-resuscitation surgical theatre teams 2 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of good teamwork for HCP's wellbeing and for patient safety is well described in the literature. 24 We speculate, if this team-spirit could have something to do with anaesthesia nurses and anaesthesiologist doing the same basic procedures, which makes it is easier to see where one can contribute. Team members are open for communication and use humour to make it a good day.…”
Section: Hcp's Perception Of Mental Strain and It's Influencing Factorsmentioning
confidence: 99%
“…Furthermore, intrahospital transfers from the emergency department have been reported to have a 33% rate of unexpected events, such as hypoxemia, arrhythmias, or cardiopulmonary arrest during the transfers [ 4 ]. Patient safety is composed of several dimensions, whereby several human factors, such as time pressure, workload, emergency situations, and organizational issues, affect intraoperative patient safety [ 5 ]. Moreover, the US Food and Drug Administration (FDA) has registered another worrying trend of over 500 alarm-related patient deaths within five years in the USA.…”
Section: Introductionmentioning
confidence: 99%